2005
DOI: 10.4049/jimmunol.175.2.1170
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Expression and Function of TLR in Lymphatic Filariasis: A Novel Mechanism of Immune Dysregulation

Abstract: Lymphatic filariasis is a disease characterized by immune dysregulation involving APC and T cell populations. To assess the contribution of TLR in mediating this dysregulation, we examined the expression of TLR1, TLR2, TLR4, and TLR9 on B cells and monocytes of filaria-infected and uninfected individuals. Baseline expression of TLR was significantly lower in B cells but not in monocytes of the filaria-infected group compared with the uninfected group. Upon stimulation with filarial Ag, a diminished up-regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 35 publications
(33 reference statements)
5
88
1
Order By: Relevance
“…Some authors have found results similar to our observations, indicating higher expression of TLR2 on PBMCs and enhanced response to the Pam3Cys ligand in Plasmodium falciparum-infected children compared with their uninfected counterparts (28). Still other reports, however, show down-regulation of TLR expression to be an important immune evasion strategy induced by some protozoan parasites (29) and observed in filaria-infected individuals (30). Interestingly, cells from uninfected subjects did not exhibit any alteration of TLR expression, suggesting that the diminished expression of TLR is a consequence of chronic Ag stimulation.…”
Section: Discussionsupporting
confidence: 78%
“…Some authors have found results similar to our observations, indicating higher expression of TLR2 on PBMCs and enhanced response to the Pam3Cys ligand in Plasmodium falciparum-infected children compared with their uninfected counterparts (28). Still other reports, however, show down-regulation of TLR expression to be an important immune evasion strategy induced by some protozoan parasites (29) and observed in filaria-infected individuals (30). Interestingly, cells from uninfected subjects did not exhibit any alteration of TLR expression, suggesting that the diminished expression of TLR is a consequence of chronic Ag stimulation.…”
Section: Discussionsupporting
confidence: 78%
“…In fact, monocyte dysfunction in filarial infection is one of several mechanisms proposed to explain parasite antigen-specific T cell hyporesponsiveness seen with patent lymphatic filariasis (19). It has previously been demonstrated that monocytes from filaria-infected individuals are studded with internalized filarial antigens, have diminished expression of genes involved in antigen presentation and processing, and produce fewer proinflammatory cytokines in response to surface receptor cross-linking (19,20).…”
mentioning
confidence: 99%
“…Most recently, defective monocyte responses toward TLR ligands have been described in filariasis patients (8), highlighting a novel form of filarial-driven immune dysregulation with important implications for the readiness of the innate immune system to respond appropriately toward pathogens, vaccines, or allergens. Effective regulation of innate inflammation is important to prevent collateral damage to host tissues and chronic inflammatory disease.…”
mentioning
confidence: 99%